Alternatives to opioid protocols in Colorado emergency departments reduce opioid use without changing reported pain. Issue 6 (12th October 2020) - Stader, Donald; Wald, Heidi; Rossi MacKay, Diane; Mannerings, Alexandra; Valuck, Robert; Kuljis, Dominick; Brady, Mark F.
Abstract: Objective: The objective of this study was to determine whether instituting an alternative to opioids (ALTO) protocol significantly reduced opioid use in emergency departments (EDs). The secondary objective was to determine whether patient‐reported pain and satisfaction were affected. Methods: Electronic health records for 10 EDs in Colorado were retrospectively examined for the 6 months before the intervention and for the same 6 months the following year after the intervention, which consisted of systemic and educational initiatives in line with the Colorado American College of Emergency Physicians 2017 Opioid Prescribing and Treatment Guidelines . Results: Of the total preintervention and postintervention unique patient visits, 47.2% received 1 of the drugs of interest, an opioid or ALTO, while in the ED. In aggregate, the EDs decreased opioid usage, measured in morphine equivalent units per 1000 ED visits, by 37.4% (95% confidence interval, 33.6%–76.2%; P < 0.0001) after the intervention. Statistically significant decreases were seen in every type of opioid. Statistically significant increases in ALTO usage were also noted across all study hospitals. There were no significant changes observed in Hospital Consumer Assessment of Healthcare Providers and Systems patient satisfaction scores before and after the intervention in the hospitals with Hospital Consumer Assessment of Healthcare Providers and Systems data (preintervention mean, 3.74; postintervention mean, 3.74; P = 0.637), and there was a small but statistically significant improvement in pain scores (preintervention mean, 3.62; postintervention mean, 3.66; P = 0.002). In a subgroup analysis of patients presenting with chief complaints of long bone fractures and malignant neoplasms, there were no significant reductions in opioid use. Conclusions: This study demonstrated the feasibility and effectiveness of implementing ALTO protocols to reduce opioid use in the ED setting without an overall reduction in patient perception of pain or satisfaction with care.